Dialogues between Science Education, Rural Education, and Decoloniality: An Analysis of Brazilian Academic Production (2002 to 2022) - Thallita Nascimento da Silva; Samuel Molina Schnorr (Revista Brasileira de Educação do Campo)
This research reviews the literature on the intersection between science education and rural education, focusing on the presence of decoloniality and traditional knowledge of the countryside in publications from the Brazilian Journal of Rural Education (RBEC) and the proceedings of the National Meeting of Research in Science Education (ENPEC) between 2002 and 2022. The objective is to investigate how these themes are represented in academic productions. A total of 98 works were analyzed, identifying 50 that address decoloniality, with 29 from ENPEC and 21 from RBEC. Although only a few works directly mention decoloniality, many use related terms such as traditional and popular knowledge. The results indicate a significant presence of decoloniality, suggesting a paradigm shift in education research, which begins to value the voices and perspectives of rural communities. The research concludes that despite the advances, there is still room to deepen the recognition and integration of traditional knowledge in science education, promoting a more inclusive and representative education of the diverse epistemologies of the countryside.